Dark Clouds and Silver Linings: An Epistemological Lens on Disaster Recovery. Issue 2 (2nd April 2020) - Missingham, Roxanne; Fletcher, Janet
ABSTRACT: Changing environmental conditions are creating conditions that are leading to an increasing number of disasters. University libraries are at risk of impact from these disasters. The nature of library collections and services is highly intertwined with the physical spaces within the institutions. Thus, the consequences of these disasters have a significant effect on the knowledge ecosystem. Epistemological theories have rarely been explored and yet are important theoretical foundations to frame disaster recovery activities. Traditionally disaster management and recovery have lacked theoretical frameworks and been operationally focused. Approaches have been based on a rationalist framing of the problem and a presumption that there is a justified truth belief that the previous state is the ideal state. In this article, the nature of knowledge through three epistemological approaches is explored and tested on two case studies. Victoria University of Wellington (New Zealand) and the Australian National University (Australia) are used to assess the operational and epistemological issues of disaster recovery. The paper reflects on challenges to the role of the library and the application of epistemological theories to learn lessons for future approaches to disaster recovery. It poses questions about how libraries can take the opportunity to rethink in the digital environment.